PVDF (Polyvinylidene Fluoride)-coated Zn3 (HHTP) 2 nano-fiber composite film for friction nano-generator and preparation method thereof
By using PVDF@Zn3(HHTP) 2 nanofiber composite film as the friction layer, the problem that traditional energy supply methods are difficult to meet the needs of wearable electronic products is solved, and the high output power and low internal resistance of friction nanogenerators are achieved, and its application in the energy supply of micro electronic devices and wearable devices has been expanded.
Patent Information
- Application Number
- CN202411828180.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-28
AI Technical Summary
Traditional energy supply methods are difficult to meet the lightweight, miniaturization and long-term energy supply needs of wearable consumer electronics, and friction nanogenerators have challenges in increasing output power.
PVDF@Zn3(HHTP) 2 nanofiber composite film was used as the friction layer, and PVDF powder was dissolved through a mixed solution of DMF and acetone, and the ground Zn3(HHTP) 2 powder was added. The composite film was prepared by sonication and electrospinning, which was used to build a high-performance friction nanogenerator.
It improves the output current of the friction nanogenerator, reduces the internal resistance of the device, enhances the charge trapping and retention capabilities, and expands its application potential in the power supply of micro electronic devices and wearable devices.
Smart Images

Figure CN119531043A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of new energy devices, and in particular relates to a PVDF@Zn3(HHTP)2 nanofiber composite film for a friction nanogenerator and a preparation method thereof. Background Art
[0002] In recent years, with the continuous innovation of technologies such as computers, the Internet of Things, and microelectronic devices, the market for wearable consumer electronic products has continued to expand. However, traditional energy supply methods cannot meet the goals of wearable consumer electronic products such as lightweight, miniaturization, and long-term energy supply. Against this background, friction nanogenerators (TENGs) came into being and have been applied and developed in the fields of anti-corrosion, medical treatment, wearable devices, and smart sensing. Today, researchers are committed to improving the output power of friction nanogenerators to meet the demand scenarios for powering microelectronic devices and expand their application areas. With the advent of more and more new materials with excellent performance, the types of friction layers of friction nanogenerators are also increasing.
[0003] Among them, the metal organic framework material Zn3(HHTP)2 is composed of metal ions Zn 2+ A highly ordered porous crystalline material with a multi-layer hexagonal stacking structure that is self-assembled through coordination bonds with the organic ligand HHTP (2,3,6,7,10,11-hexahydroxytriphenyl). Among them, Zn3(HHTP)2 has a unique hexagonal porous structure and a high specific surface area, providing more charge capture sites for the friction layer. In addition, due to the strong d-π orbital conjugation of the metal node and hexahydroxytriphenyl, it has a certain conductivity, which is very beneficial for reducing the internal resistance of the friction nanogenerator and increasing the output power when an external load is connected. Summary of the invention
[0004] The main purpose of the present invention is to provide a method for preparing a PVDF@Zn3(HHTP)2 nanofiber composite film for a friction nanogenerator, which has relatively low requirements on production equipment, a simple process flow and mild experimental conditions.
[0005] Another object of the present invention is to provide a PVDF@Zn3(HHTP)2 nanofiber composite film for a friction nanogenerator.
[0006] Another object of the present invention is to provide a friction nanogenerator comprising the PVDF@Zn3(HHTP)2 nanofiber composite film.
[0007] The above-mentioned object of the present invention is achieved by the following technical solutions:
[0008] The present invention provides a method for preparing a PVDF@Zn3(HHTP)2 nanofiber composite film for a triboelectric nanogenerator, comprising the following steps:
[0009] (1) DMF and acetone (ACE) are mixed in a certain proportion, and PVDF powder is added. The mixture is sealed and placed in an oven to dissolve at 60°C for 4 hours to fully dissolve the PVDF powder and to make the mixed solution transparent and free of bubbles, thereby obtaining a spinning solution;
[0010] (2) Grinding Zn3(HHTP)2 powder, adding it to the spinning solution in step (1), stirring and ultrasonically treating for 30 minutes, and uniformly dispersing it;
[0011] (3) The spinning solution is transferred into a syringe and bubbles are removed, and a needle is installed for electrospinning;
[0012] (4) After spinning, cut into small-sized films.
[0013] Preferably, in step (1), the mass ratio of DMF to acetone is 3:2.
[0014] Preferably, in step (2), the mass ratio of Zn3(HHTP)2 powder to PVDF powder in the mixed solution is 1:1-100.
[0015] Preferably, in step (4), the size of the small-sized film is (1-6)×(1-6) cm 2 .
[0016] Preferably, in step (4), the thickness of the PVDF@Zn3(HHTP)2 nanofiber composite film for the friction nanogenerator is 30 to 350 μm.
[0017] The present invention also provides a PVDF@Zn3(HHTP)2 nanofiber composite film for a friction nanogenerator, which is prepared by any of the above preparation methods.
[0018] The present invention also provides a high-performance friction nanogenerator, and its preparation method comprises: using a PVDF@Zn3(HHTP)2 nanofiber composite film for the friction nanogenerator to paste aluminum foil on one side as an electrode, and using copper conductive glue to draw out current, as a negative electrode; taking a PA film of the same size to paste aluminum foil on one side as an electrode, and using copper conductive glue to draw out current as a positive electrode.
[0019] Preferably, the high-performance friction nanogenerator is a vertical contact-separation friction nanogenerator, in which the positive electrode and the negative electrode are in a separated state, and when the positive and negative electrodes perform contact and separation movement under the action of an external force of a certain frequency, an alternating current signal with the same frequency as the external force is obtained.
[0020] The composite film of the present invention introduces Zn3(HHTP)2 as a filler, so that the composite film not only has the excellent performance of MOF itself, but also has certain thermal stability and chemical stability. The added Zn3(HHTP)2 powder improves the contact performance between the positive and negative electrodes of the friction nanogenerator by changing the surface roughness of the PVDF film. At the same time, the addition of Zn3(HHTP)2 powder effectively improves the dielectric properties of the film, improves the ability of the film to retain charge, and reduces charge loss. In addition, Zn3(HHTP)2 with semiconductor properties not only provides more charge capture sites, but also improves the conductivity of the film, reduces the overall internal resistance of the device, and improves the output power of the device. These effects are verified through detailed electrical tests and theoretical analysis.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The preparation method of the PVDF@Zn3(HHTP)2 nanofiber composite film of the present invention is simple in process and is conducive to mass production.
[0023] (2) The high-performance friction nanogenerator based on the PVDF@Zn3(HHTP)2 nanofiber composite film of the present invention adopts a hydrothermal synthesis method to prepare Zn3(HHTP)2 powder, which is mixed with a PVDF electrospinning solution and then electrospun to prepare a PVDF@Zn3(HHTP)2 nanofiber composite film. Subsequently, the PVDF@Zn3(HHTP)2 nanofiber composite film is cut into a specific size and then pasted with aluminum foil, and then assembled with a PA film into a vertical contact-separation friction nanogenerator. When the positive and negative poles perform contact-separation motion under the action of an external force of a certain frequency, an alternating current signal with the same frequency as the external force is obtained.
[0024] (3) In terms of mechanical energy recovery and conversion, the present invention can recover low-frequency mechanical energy in the surrounding environment and convert it into electrical energy, which can be used to directly light up LED lights or charge commercial capacitors to store electrical energy. It is a green and environmentally friendly energy device with good practicality and can provide new energy supply solutions for microelectronic devices and wearable devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the SEM image of Zn3(HHTP)2 powder in Example 1 (scale bar: 500 nm).
[0026] Figure 2 Schematic diagram of the structure of the vertical contact-separation friction nanogenerator in Example 1; wherein 1 is aluminum foil, 2 is PA film, 3 is copper conductive adhesive, 4 is PVDF@Zn3(HHTP)2 nanofiber composite film, and 5 is aluminum foil.
[0027] Figure 3 The output performance of the friction nanogenerator made of composite films with different contents of Zn3(HHTP)2 in the examples. DETAILED DESCRIPTION
[0028] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art may make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the claims of the present application equally.
[0029] The Zn3(HHTP)2 powder used in the following examples was prepared by the following method: 57 mg 2,3,6,7,10,11-hexahydroxytriphenyl and 90 mg zinc acetate were added to a 30 mL glass bottle and dissolved in 14 mL deionized water, followed by ultrasonication for 15 min to obtain a dark blue solution. After the ultrasonication was completed, the glass bottle was placed in an 85 ° C oven for 20 h, and the reaction was naturally cooled after completion. After the reaction was completed, deionized water was used for washing and centrifugation was performed. After the water washing was completed, acetone was used for washing and centrifugation was performed. Each of the above washing processes was repeated at least three times until the upper solution became clear and transparent. During centrifugation, the centrifuge speed was set to 8000 rpm and the centrifugation time was 8 min. After washing, the sample was placed in a 70 ° C vacuum drying oven and dried for 12 h to obtain a black powder Zn3(HHTP)2.
[0030] Example 1
[0031] 360 mg of ground Zn3(HHTP)2 powder was dispersed into 20 g of prepared PVDF spinning solution, with a mass ratio of Zn3(HHTP)2 powder to PVDF powder of 1:10, and stirred and ultrasonicated for 30 min. The mixed spinning solution was transferred into a syringe for electrospinning to obtain a PVDF@Zn3(HHTP)2 nanofiber composite film (thickness: 100 μm). The microscopic morphology of Zn3(HHTP)2 is shown in Figure 2. Figure 1 shown.
[0032] Subsequently, the obtained PVDF@Zn3(HHTP)2 nanofiber composite film was cut into small-sized films of 1.5 cm×1.5 cm, and aluminum foil was pasted on one side of the small-sized film as an electrode, and copper conductive glue was used to draw out the current to obtain the negative electrode of the friction nanogenerator; a PA film of the same size was taken and aluminum foil was pasted on one side as an electrode, and copper conductive glue was used to draw out the current to serve as the positive electrode of the friction nanogenerator. The positive electrode and the negative electrode together formed a vertical contact-separation friction nanogenerator, such as Figure 2 shown.
[0033] After testing, the output current of the vertical contact-separation friction nanogenerator is 11.8μA, which is the highest among pure PVDF films ( Figure 3 The output of the triboelectric nanogenerator assembled from the Pure in the sample was 2.26 times that of the pure nanogenerator assembled from the sample. This experimental result confirms that the PVDF@Zn3(HHTP)2 nanofiber composite film is beneficial to improving the output performance of TENG.
[0034] Example 2
[0035] 120 mg of ground Zn3(HHTP)2 powder was dispersed into 20 g of prepared PVDF spinning solution, with a mass ratio of Zn3(HHTP)2 powder to PVDF powder of 1:30, and stirred and ultrasonicated for 30 minutes. The mixed spinning solution was transferred into a syringe for electrospinning to obtain a PVDF@Zn3(HHTP)2 nanofiber composite film.
[0036] Subsequently, the obtained PVDF@Zn3(HHTP)2 nanofiber composite film was cut into small-sized films of 1.5 cm×1.5 cm, and a friction nanogenerator was obtained using the same method as in Example 1.
[0037] After testing, the output current of the friction nanogenerator prepared in this embodiment is 6.4μA. This result occurs because the amount of Zn3(HHTP)2 added is too small, resulting in a small improvement in the performance of the composite film by Zn3(HHTP)2, thus failing to significantly improve the output performance of the friction nanogenerator.
[0038] Example 3
[0039] 240 mg of ground Zn3(HHTP)2 powder was dispersed into 20 g of prepared PVDF spinning solution, with a mass ratio of Zn3(HHTP)2 powder to PVDF powder of 1:15, and stirred and ultrasonicated for 30 minutes. The mixed spinning solution was transferred into a syringe for electrospinning to obtain a PVDF@Zn3(HHTP)2 nanofiber composite film.
[0040] Subsequently, the obtained PVDF@Zn3(HHTP)2 nanofiber composite film was cut into small-sized films of 1.5 cm×1.5 cm, and a friction nanogenerator was obtained using the same method as in Example 1.
[0041] After testing, the output current of the friction nanogenerator prepared in this embodiment is 8.6 μA. This result occurs because the amount of Zn3(HHTP)2 added is small, so that the performance improvement of the composite film by Zn3(HHTP)2 molecules is limited.
[0042] Example 4
[0043] 480 mg of ground Zn3(HHTP)2 powder was dispersed into 20 g of prepared PVDF spinning solution, with a mass ratio of Zn3(HHTP)2 powder to PVDF powder of 1:7.5, and stirred and ultrasonicated for 30 min. The mixed spinning solution was transferred into a syringe for electrospinning to obtain a PVDF@Zn3(HHTP)2 nanofiber composite film.
[0044] Subsequently, the obtained PVDF@Zn3(HHTP)2 nanofiber composite film was cut into small-sized films of 1.5 cm×1.5 cm, and a friction nanogenerator was obtained using the same method as in Example 1.
[0045] After testing, the output current of the triboelectric nanogenerator prepared in this embodiment is 7.0μA. This result is due to the large amount of Zn3(HHTP)2 added, and a small amount of Zn3(HHTP)2 powder agglomerates, which reduces the device's ability to store charge. Although the increase in the amount of Zn3(HHTP)2 added reduces the output performance of TENG, it is still better than pure PVDF.
[0046] Example 5
[0047] 600 mg of ground Zn3(HHTP)2 powder was dispersed into 20 g of prepared PVDF spinning solution, with a mass ratio of Zn3(HHTP)2 powder to PVDF powder of 1:6, and stirred and ultrasonicated for 30 min. The mixed spinning solution was transferred into a syringe for electrospinning to obtain a PVDF@Zn3(HHTP)2 nanofiber composite film.
[0048] Subsequently, the obtained PVDF@Zn3(HHTP)2 nanofiber composite film was cut into small-sized films of 1.5 cm×1.5 cm, and a friction nanogenerator was obtained using the same method as in Example 1.
[0049] After testing, the output current of the triboelectric nanogenerator prepared in this embodiment is 6.0μA. This result is due to the excessive addition of Zn3(HHTP)2, which makes it difficult to disperse evenly in the spinning solution and easily forms agglomerates. The deterioration of spinning performance reduces the triboelectric performance of the device, which in turn leads to a decrease in the output performance of TENG. Although the increase in the amount of Zn3(HHTP)2 added reduces the output performance of TENG, it is still better than that of pure PVDF.
[0050] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing a PVDF@Zn3(HHTP)2 nanofiber composite film for a triboelectric nanogenerator, characterized in that: The following steps are involved: (1) DMF and acetone are mixed in proportion, PVDF powder is added, the mixture is sealed and placed in an oven to dissolve at 60° C. for 4 h, so that the PVDF powder is fully dissolved and the mixed solution is transparent and free of bubbles, thereby obtaining a spinning solution; (2) After grinding, Zn3(HHTP)2 powder was added to the spinning solution in step (1), stirred and ultrasonically treated for 30 min to uniformly disperse; (3) The spinning solution is transferred into a syringe and bubbles are removed, and a needle is installed for electrospinning; (4) After spinning, cut into small-sized films.
2. The method for preparing the PVDF@Zn3(HHTP)2 nanofiber composite film for the triboelectric nanogenerator according to claim 1, characterized in that: In step (1), the mass ratio of DMF to acetone is 3:
2.
3. The method for preparing the PVDF@Zn3(HHTP)2 nanofiber composite film for the triboelectric nanogenerator according to claim 1, characterized in that: In step (2), the mass ratio of Zn3(HHTP)2 powder to PVDF powder in the mixed solution is 1:1-100.
4. The method for preparing the PVDF@Zn3(HHTP)2 nanofiber composite film for the triboelectric nanogenerator according to claim 1, characterized in that: In step (4), the size of the small-sized film is (1-6)×(1-6) cm 2 .
5. The method for preparing the PVDF@Zn3(HHTP)2 nanofiber composite film for the triboelectric nanogenerator according to claim 1, characterized in that: In step (4), the thickness of the PVDF@Zn3(HHTP)2 nanofiber composite film for the friction nanogenerator is 30 to 350 μm.
6. A PVDF@Zn3(HHTP)2 nanofiber composite film for a triboelectric nanogenerator, characterized in that: The nanofiber composite film is prepared by the method for preparing the PVDF@Zn3(HHTP)2 nanofiber composite film for a friction nanogenerator according to any one of claims 1 to 5.
7. A high-performance friction nanogenerator, characterized in that: The preparation method comprises: gluing aluminum foil to one side of the PVDF@Zn3(HHTP)2 nanofiber composite film of the friction nanogenerator as an electrode, and using copper conductive glue to draw out current, as a negative electrode; taking a PA film of the same size and gluing aluminum foil to one side as an electrode, and using copper conductive glue to draw out current as a positive electrode.
8. The high-performance triboelectric nanogenerator according to claim 7, characterized in that: The high-performance friction nanogenerator is a vertical contact-separation friction nanogenerator.
9. The high-performance triboelectric nanogenerator according to claim 8, characterized in that: The positive pole and the negative pole are in a separated state. When the positive and negative poles make contact and separation movements under the action of an external force of a certain frequency, an alternating current signal with the same frequency as the external force is obtained.
Citation Information
Patent Citations
PDMS@F-MOF composite film for friction nanometer generator and preparation method for PDMS@F-MOF composite film
CN111087635A
PVDF@KUAST-8 nanofiber composite film for friction nanogenerator and preparation method of film
CN111118619A
Preparation method and application of MOF material PVDF-HFP gel electrolyte
CN113054249A
Preparation method of self-repairing electromagnetic wave shielding composite film based on conductive MOFs
CN118834421A
Preparation method of high-stability and high-adsorption MOF nanofiber membrane
CN118895609A